Камень власти: роман / Ольга Елисеева - Елисеева Ольга Игоревна (Век золотой Екатерины, 2009)
Экземпляры: ф.18 (20220329) / Инвентарный номер: 3992 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Е 51 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-442